Development and application of electric arc furnace combined blowing technology. (13th September 2016) - Ma, G.; Zhu, R.; Dong, K.; Li, Z.; Liu, R.; Yang, L.; Wei, G.
Abstract : A number of electric arc furnace (EAF) plants in China use high proportions of hot metal in the charge because of availability of excess liquid iron at the steelworks and/or because of the high price of scrap relative to hot metal. Liquid steel costs are still higher than the basic oxygen furnace as the EAF is not as efficient when refining liquid iron. EAF combined blowing technology has been modelled and installed in industrial plants with the aim of increasing stirring and hence improving refining. The industrial application of the combined blowing technology in a number of steel plants indicates that the combined blowing technology of EAF can effectively improve the pool stirring strength and reaction dynamics condition of the molten pool, and optimise production.